TNF superfamily members promote hepatitis C virus entry via an NF-κB and myosin light chain kinase dependent pathway - Fletcher, N; Clark, A; Balfe, P; McKeating, J (Microbiology Society, 2017)
Preventing virally induced liver disease begins with an understanding of the host factors that define susceptibility to infection. Hepatitis C virus (HCV) is a global health issue, with an estimated 170 million infected individuals at risk of developing liver disease including fibrosis and hepatocellular carcinoma. The liver is the major reservoir supporting HCV replication and this hepatocellular tropism is defined by HCV engagement of cellular entry receptors. Hepatocytes are polarized in vivo and this barrier function limits HCV entry. We previously reported that activated macrophages promote HCV entry into polarized hepatocytes via a TNF-α-dependent process; however, the underlying mechanism was not defined. In this study, we show that several TNF superfamily members, including TNF-α, TNF-β, TWEAK and LIGHT, promote HCV entry via NF-κB-mediated activation of myosin light chain kinase (MLCK) and disruption of tight junctions. These observations support a model where HCV hijacks an inflammatory immune response to stimulate infection and uncovers a role for NF-κB-MLCK signalling in maintaining hepatocellular tight junctions.